Practical grammar of modern Chinese II. Function words - Liu, Yuehua, 1937-; Pan, Wenyu; Gu, Wei, 1932- (London : Routledge, 2021)
Chinese grammar is characterized by its simple structure, lack of inflections, and wide use of monosyllabic morphemes. With the increasing popularity of learning Chinese as a second language, there is a demand for a guide to Chinese grammar that's targeted at second language learners. This four-volume set is one of the earliest and most influential works on Chinese grammar, with a special focus on teaching and learning Chinese as a second language. Utilizing their rich teaching experience, the authors analyze a myriad of authentic examples to describe the Chinese grammatical phenomenon and rules. This volume introduces the functional words in modern Chinese grammar, which include prepositions, conjunctions, auxiliary verbs, onomatopoeia, and interjections. Since the first edition came out in 1983, this set has been revised twice and remained one of the best sellers in this topic. Practitioners and scholars of teaching Chinese as a second language, as well as students with a basic knowledge of Chinese, will find it a handy reference.
1 Preposition. 2 Conjunction. 3 Auxiliary. 4 Onomatopoetic Word. 5 Interjection
OCLC-licensed vendor bibliographic record.
Keywords: Chinese language -- Grammar; LANGUAGE ARTS & DISCIPLINES / Grammar